Comparison of intercept trap fluids and aerial spore collectors to survey fungal spores - Bérubé, Jean A.; Allison, Jeremy D.; Van Rooyen, Kate; Hughes, Cory; Gagné, Patrick N.; Ochoa, Isabelle; Sweeney, Jon (Frontiers in Forests and Global Change, 2022)
Surveillance for early detection of non-native, invasive pathogens requires simple, sturdy, and easy to use collecting devices. In this study, we compared the fungal species detected in wet collection cups of Lindgren traps versus those detected on slides with oiled cheesecloth as aerial spore collectors. DNA was extracted and amplified from both using the primers ITS1F - gITS7, and Illumina sequencing was used for metabarcoding of fungi present in samples. In 90 samples there were 1277 fungal operational taxonomic units (OTUs). For fungal OTUs only detected by one collection method, insect traps had three times the number of fungal OTUs compared to slides, and this pattern persisted when analyses were restricted to pathogens and forest pathogens. Annually, thousands of insect traps are deployed in North America and the associated trap fluids have added value in forest disease research and monitoring.